Factors that Influence Academic Resilience of Students from Economically Disadvantaged Environments in South Africa During the COVID-19 Era - Segun Emmanuel Adewoye (Journal of Education and Learning Technology)
Many students from economically disadvantaged backgrounds faced challenges in their academic prospects even prior to the COVID-19 pandemic, as a result of risk factors both in the family and school environments. Despite these challenges, some learners from economically disadvantaged areas in South Africa go on to achieve academically, while others succumb to risk factors. The purpose of this study was to examine factors that influence the academic resilience of students from economically disadvantaged environments in South Africa during the COVID-19 Era. A phenomenological research design was adopted using a qualitative research approach. A non-random purposive sampling technique was used to identify 20 adolescent school learners within the age bracket of 12 to 14 from underprivileged backgrounds to participate in the study. Data was collected using semi-structured individual interviews which were also audio-recorded. Following recordings, the interviews were transcribed. The data was analysed using inductive thematic analysis. The findings of this study revealed that optimism and hopefulness, determination and perseverance, internal locus of control and family support were the resilient factors that contributed to the academic resilience of learners from economically disadvantaged environments during the COVID-19 pandemic. The broad implication of these findings is that students from economically disadvantaged backgrounds can succeed academically if they leverage their resilience on internal and external protective factors. By providing insight into the factors that enhance academic resilience, parents and teachers can help learners build the resilience needed to persevere through academic difficulties and succeed in their educational journey.